Kevin Symonds, On the Third Part of the Secret of Fatima (St. Louis, MO: En Route Books and Media 2017) - Mielnik, Dawid (Verbum Vitae, 2021)
Review of the book: Kevin Symonds, On the Third Part of the Secret of Fatima (St. Louis, MO: En Route Books and Media 2017). Pp. 582, ISBN: 978-1-950108-23-7.